Major clinical approaches to endodontic treatment in the treatment scenario of patients with head and neck cancer: a systematic review - Nascimento Junior, Ademilton Couto (2025)
Introduction: In the context of endodontic treatments and cancer, head and neck squamous cell carcinoma is the 6th most common form of cancer in the world, with more than 400,000 deaths annually. The great challenge is endodontic treatment after radiotherapy processes. Furthermore, the promising applications of exosomes in targeted therapy and we propose future directions for the use of exosomes in clinical and endodontic treatment. Objective: The present study developed a systematic review to elucidate the main clinical approaches to endodontic treatment in the treatment scenario of patients with head and neck cancer. Methods: The PRISMA Platform systematic review rules were followed. The search was carried out from July to September 2024 in the Scopus, PubMed, Science Direct, Scielo, and Google Scholar databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results and Conclusion: A total of 124 articles were found, 35 articles were evaluated in full and 20 were included and developed in the present systematic review study. Considering the Cochrane tool for risk of bias, the overall assessment resulted in 25 studies with a high risk of bias and 22 studies that did not meet GRADE and AMSTAR-2. Most studies did not show homogeneity in their results, with X2=89.2%<50%. It was concluded that biomechanical preparation using a reciprocating system and 2.5% NaOCl in irradiated teeth demonstrated efficacy in reducing endodontic contaminants. Moreover, Ca(OH)2 as intracanal medication should be performed in irradiated patients with infected root canals. Also, radiotherapy causes changes in pulp behavior patterns in the short term; however, recovery and return to mean values occur after long periods. The probiotic SsK12 significantly reduced the incidence, onset, and duration of severe oral mucositis with a good safety profile. Artificial intelligence has valuable applications in the field of modern endodontics with promising results, especially in endodontic treatments in patients with head and neck cancer.